The role of union health and safety representatives during the COVID‐19 pandemic: A case study of the UK food processing, distribution, and retail sectors. Issue 4 (15th July 2022) - Cai, Minjie; Moore, Sian; Ball, Chris; Flynn, Matt; Mulkearn, Ken
Abstract: This article highlights the weakness of the UK's occupational health and safety infrastructure exposed by the COVID‐19 pandemic. Utilising a political economy perspective, it captures the critical role of workplace union safety representatives in mitigating risk and contesting the expropriation of health and recommodification of labour, specifically inadequate sick pay.